14.5k views
2 votes
3 5/6= 1 2/3+ H. Substitute 2 1/6 for H

User Bimzee
by
5.0k points

1 Answer

4 votes


\mathrm{H}=2 (1)/(6) is correct value of expression
3 (5)/(6)=1 (2)/(3)+\mathrm{H}

Solution:

Given expression is
3 (5)/(6)=1 (2)/(3)+\mathrm{H}

We have to substitute
2(1)/(6) for H

We have to substitute the value into the given expression and determine whether the given value of "H" makes the sentence true

On substituting given value of H in equation (1) and solving Right Hand Side, we get,


1 (2)/(3)+2 (1)/(6)

Now let us convert the mixed fractions,


1 (2)/(3)+2 (1)/(6)=(3 * 1+2)/(3)+(6 * 2+1)/(6)=(5)/(3)+(13)/(6)

On solving we get,


(5)/(3)+(13)/(6)=(10+13)/(6)=(23)/(6)

Thus we have solved R.H.S and got the value
(23)/(6)

Now let us solve L.H.S of expression,


3 (5)/(6)=(6 * 3+5)/(6)=(18+5)/(6)=(23)/(6)

Thus L.H.S and R.H.S are equal

Thus given "H" =
2(1)/(6) makes the expression true

User Corrine
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.